Comparison Of Irms Delhi Methodology With Who Methodology On Immunization Coverage - Singh Padam (Wolters Kluwer Medknow Publications, 1996)
Research question: What are the merits of IRMS Model over WHO Model for Coverage Evaluation Survey? Which method is superior and appropriate for coverage evolution survey of immunization in our setting? Objective: To compare IRMS Delhi methodology with WHO methodology on Immunization Coverage. Study Design: Cross-Sectional Setting: Urban and Rural both. Participants: Mothers& Children Sample Size: 300 children between 1-2 years and 300 mothers in rural areas and 75 children and 75 mothers in urban areas. Study Variables: Rural, Urban, Cast-Group, Size of the stratum, Literacy, Sex and Cost effectiveness. Outcome Variables: Coverage level of immunization. Analysis: Routine Statistical Analysis. Results: IRMS developed methodology scores better rating over WHO methodology, especially when coverage evolution is attempted in medium size villages with existence of socio-economic seggregation-which remains the main characteristic of the Indian villages.